2020
DOI: 10.1111/1346-8138.15623
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of co‐culture of human induced pluripotent stem cell‐derived melanocytes and keratinocytes in vitro

Abstract: Dear Editor,We previously established human induced pluripotent stem (iPS) cell-derived melanocytes in large quantities within a short period and induced their differentiation and high melanogenic potency using original iPS cell-derived melanocyte medium (iDMM). 1 We used original iPS cell lines established from T cells in the blood of a healthy 40-year-old Japanese man and a Sendai virus vector. 1 In the present study, we established melanocytes derived from more general iPS cells (1383D6, HPS1006) obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…It has been demonstrated that induced pluripotent stem (iPS) cells have the ability to differentiate into multiple cell types in the body and have an unlimited growth potential. A number of approaches have been used to establish human iPS cell‐derived melanocytes 41–44 . We established human iPS cell‐derived melanocytes from T cells in the blood of healthy persons and vitiligo patients and a Sendai virus vector using original iPS cell‐derived melanocyte medium (advanced iDMM) (Figure 2).…”
Section: Stem Cell Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been demonstrated that induced pluripotent stem (iPS) cells have the ability to differentiate into multiple cell types in the body and have an unlimited growth potential. A number of approaches have been used to establish human iPS cell‐derived melanocytes 41–44 . We established human iPS cell‐derived melanocytes from T cells in the blood of healthy persons and vitiligo patients and a Sendai virus vector using original iPS cell‐derived melanocyte medium (advanced iDMM) (Figure 2).…”
Section: Stem Cell Methodsmentioning
confidence: 99%
“…We mechanically isolated human iPS cell‐derived melanocyte colonies from those dishes by picking them up gently with a pipette. These mechanically isolated colonies were then transferred to new gelatinous dishes coated with Matrigel and were cultured with advanced iDMM 43,44 . Previous approaches to grow and differentiate iPS cells into melanocytes needed first to produce embryoid bodies and then to process them to differentiate into melanocytes, 41,42 which took approximately 30 days.…”
Section: Stem Cell Methodsmentioning
confidence: 99%
See 3 more Smart Citations